Jean Aitchison, Words in the mind. An introduction to the mental lexicon. Blackwell, Oxford, 1987; 229 pp. - Río, Norma del (El Colegio de México, 1994)
Se reseñó el libro: Words in the mind. An introduction to the mental lexicon.